The Social Construction of Food Security and Wage Practices in the Halal Tourism Ecosystem: An Interpretive Study Based on Maqashid Shariah - Novi Yanti Sandra Dewi; Ahadiah Agustina (Lembaga Bale Literasi, 2026)
This study examines how food security and wage practices are socially constructed within the halal tourism ecosystem from a maqashid shariah perspective. Despite the rapid growth of halal tourism, existing studies largely emphasize certification, destination competitiveness, and market expansion, while the substantive dimensions of welfare, particularly food security and wage justice, remain underexplored. This research employs a qualitative method with an interpretivist paradigm to capture the lived experiences and meanings constructed by actors within the halal tourism ecosystem in Mataram City, Indonesia. Data were collected through in-depth interviews, direct observation, and documentation involving 20 purposively selected informants, including tourism business actors, workers, local communities, and institutional stakeholders. The findings reveal that food security is not merely determined by the availability of halal products but is socially constructed through access, affordability, and price stability, which are often disrupted by tourism driven market dynamics. Similarly, wage practices are characterized by informality, instability, and dependence on tourist flows, resulting in limited alignment with principles of fairness and adequacy. From a maqashid shariah perspective, these conditions indicate that the realization of hifz al-nafs (protection of life) and hifz al-mal (protection of wealth) remains partial. The study highlights a gap between the symbolic implementation of halal principles and their substantive realization in socio economic practices. This research contributes to the literature by integrating social construction theory and maqashid shariah in analyzing welfare dimensions within halal tourism and suggests the need for more inclusive, justice oriented policy frameworks that address both economic growth and community well being.